Aprovechamiento de la potencia excedente de los motores eléctricos en Nutrilácteos El Roble (2021)
In Chiquinquirá Boyacá, Colombia, is located the Plant "Nutrilácteos El Roble"; that as part of its production process it uses electrical energy whose value billed by the company providing the service is excessive, with an annual average of $ 15,191,762, increasing production costs and reducing profits of the company. T